Patai's Chemistry of Functional Groups 2009
DOI: 10.1002/9780470682531.pat0232
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Complexes of Dienes and Polyenes

Abstract: 1. Introduction2. Structure and Bonding3. NMR Spectroscopic Characterization and Fluxional Behavior4. Preparation and Isomerizations of Conjugated Diene Complexes5. Reactions of Conjugated Diene Complexes6. Preparation of Cyclobutadiene–Metal Complexes7. Reactions of Cyclobutadiene–Metal Complexe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 452 publications
0
2
0
Order By: Relevance
“…Since Reihlen and co-workers first reported the complex Fe­(CO) 3 (η 4 -1,3-butadiene) in 1930, chemists have been fascinated by the ability of transition metals to influence the physical and chemical properties of conjugated polyenes . The vast majority of these studies have focused on η 4 -, η 5 -, and η 6 -coordinated polyenes, with some of the most significant developments historically involving iron. , By comparison, much less is known about the properties of their η 2 -bound counterparts. Of the few complexes reported that involve nonaromatic polyenes, most are cyclooctatetraene complexes of Mn, , Cu, and Ni .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Reihlen and co-workers first reported the complex Fe­(CO) 3 (η 4 -1,3-butadiene) in 1930, chemists have been fascinated by the ability of transition metals to influence the physical and chemical properties of conjugated polyenes . The vast majority of these studies have focused on η 4 -, η 5 -, and η 6 -coordinated polyenes, with some of the most significant developments historically involving iron. , By comparison, much less is known about the properties of their η 2 -bound counterparts. Of the few complexes reported that involve nonaromatic polyenes, most are cyclooctatetraene complexes of Mn, , Cu, and Ni .…”
Section: Introductionmentioning
confidence: 99%
“… 2 The vast majority of these studies have focused on η 4 -, η 5 -, and η 6 -coordinated polyenes, with some of the most significant developments historically involving iron. 2 , 3 By comparison, much less is known about the properties of their η 2 -bound counterparts. Of the few complexes reported that involve nonaromatic polyenes, most are cyclooctatetraene complexes of Mn, 4 , 5 Cu, 6 and Ni.…”
Section: Introductionmentioning
confidence: 99%